Effects of Strain and Production-Cycle on Indices of Lysine Catabolism in Turkeys - Gatrell, S.K.; Swiger, B.N.; Engels, J.G.; Berg, L.E.; Barnard, J.T.; Mortiz, J.S.; Blemings , K.P. (International Journal of Poultry Science, 2014)
In typical turkey production diets, lysine is frequently the second limiting amino acid. Understanding its catabolism could provide opportunities to increase the efficiency of lysine use for protein synthesis. We hypothesize that indices of lysine catabolism in turkey liver vary throughout the production cycle. Two commercial strains of turkey, Strain A and B, were analyzed 8 times over a period of 17 weeks (n = 8 birds/sampling time/strain) for lysine alpha-ketoglutarate (LKR) and saccharopine dehydrogenase (SDH) activities and mRNA abundance, in vitro lysine oxidation (LOX), L-amino acid oxidase (LAAO) activity, lysyl oxidase (LO) activity and mRNA expression of cationic amino acid transporters (CAT) 1, 2 and 3. We found differences in hepatic LKR activity (p = 0.007), LKR mRNA (p = 0.0004), SDH activity (p = 0.008), LOX (p